2022
DOI: 10.1155/2022/5452942
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on the Implementation of Renewable Biodiesel Fuel for Automotive and Power Plants: Raw Materials Perspective

Abstract: The issue of energy availability and the impact of global warming has become a specific concern for researchers in various countries in the world. This condition opens up space for potential alternative energy sources that are newer and more sustainable. Biodiesel as a sustainable alternative energy can be applied directly to industrial and automotive fields and even as a fuel source for power plants. This study provides a specific overview of the use and development of biodiesel as a fuel source for renewable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 138 publications
0
5
0
Order By: Relevance
“…Tis investigation selectively used MWCNT and TiO 2 nanoparticles for enhancing waste tyre oil fuel for diesel engines and found that hybrid nanofuels outperformed diesel, waste tyre oil biodiesel, and also nanofuels. Te investigation may be extended to hybrid nanofuels with the use of some other combinations more than two kinds [33].…”
Section: Discussionmentioning
confidence: 99%
“…Tis investigation selectively used MWCNT and TiO 2 nanoparticles for enhancing waste tyre oil fuel for diesel engines and found that hybrid nanofuels outperformed diesel, waste tyre oil biodiesel, and also nanofuels. Te investigation may be extended to hybrid nanofuels with the use of some other combinations more than two kinds [33].…”
Section: Discussionmentioning
confidence: 99%
“…Constraint (5) ensures that jobs assigned to the same machine are processed without skipping queues. Each job must be processed at a single speed level in each scenario, according to (6). Constraints (7) and (8) determine the completion time of the first job and the remaining jobs in each machine under scenario w, respectively.…”
Section: ) Sets Parameters and Variablesmentioning
confidence: 99%
“…This necessitates innovative approaches to energy utilization. The generation and utilization of energy have become central issues in the context of sustainable development [5], [6]. Conventional energy sources, which are predominantly reliant on fossil fuels, are known to contribute to environmental degradation and climate change through the emission of greenhouse gases [7].…”
Section: Introductionmentioning
confidence: 99%
“…Biodiesel has a chemical composition of fatty acid alkyl esters and is a strong candidate to replace conventional petrodiesel in the future. This biofuel can contribute to the global energy crisis because of its multiple benefits, including good performance in combustion engines, low generation of polluting gases (greenhouse gases), non-or low toxicity, biodegradability, and sustainability (Sentanuhady et al 2022). Biodiesel is generally obtained using four conventional methods: direct blending or dilution, microemulsion, thermal cracking/pyrolysis, and transesterification (Velusamy et al 2021).…”
Section: Biodieselmentioning
confidence: 99%